Entering a Fantasy World through Its Map. Issue 1 (April 2018) - Ekman, Stefan
Abstract : This essay demonstrates how we can gain critical insights into a fantasy world by reading its accompanying map, using Ben McSweeney's map from Brandon Sanderson's The Rithmatist as an example. An analysis of the map's topography, linguistic signs, and surround elements is carried out in terms of Denis Wood's proposition that all maps have authors, subjects, and themes. The results show that even without reference to the text, the map comments on the fantasy world's technological level, its colonial history, and the central conflict of the story. Interpreting the map also invites a broader examination of the relationship between the fantastical and the actual.